Coefficient of friction, walking speed and cadence on slippery and dry surfaces: shoes with different groove depths. Issue 4 (2nd October 2019) - Ziaei, Mansour; Mokhtarinia, Hamidreza; Tabatabai Ghomshe, Farhad; Maghsoudipour, Maryam
Abstract : Objective . The present study aimed to determine the coefficient of friction (COF), walking speed (WS) and cadence while walking on slippery and dry surfaces using shoes with different sole groove depths to predict likelihood of fall. Background . Design of shoe sole groove is crucial to prevent slipping during walking. Methods . 22 healthy young men (mean age 24.5, body mass index 22.5) volunteered for this semi-experimental study. Six different conditions of the test (combination of three shoes and two surfaces) were defined and the condition was repeated three times. In total, 396 trials (22 subjects × 3 groove depths × 2 surfaces × 3 times) were obtained for data analysis. COF was recorded by force platform at 1000 Hz and walking parameters recorded using 3D motion analysis with six infrared cameras at 200 Hz. Results . The highest COF was obtained from the deepest groove depth (5.0 mm) on both dry and slippery surfaces. The COF on slippery surfaces was significantly lower in comparison with dry surfaces. WS and cadence were not significantly different on dry and slippery surfaces. Conclusion . The deeper groove is better to prevent slipping because the COF increases by increasing the shoe sole groove depth. WS did not change on dry and slippery surfaces.